A model for taxonomic work on homoxenous coccidia: redescription, host specificity, and molecular phylogeny of Eimeria ranae Dobell, 1909, with a review of anuran-host Eimeria (Apicomplexa: Eimeriorina) - Jirků, Miloslav; Jirků, Milan; Oborník, Miroslav; Lukes, Julius; Modrý, David (The Journal of eukaryotic microbiology, 2009)
We attempt to extend knowledge of anuran Eimeria, and to provide a model for a complex approach to studies on coccidia. New host and geographic records of coccidia in European Anura are provided. In the second part, Eimeria ranae Dobell, 1909 is redescribed from European terrestrial frogs of the genus Rana based on light microscopic and ultrastructural data on both exogenous and endogenous developmental stages, host specificity, and molecular phylogenetic data. Results of experimental transmissions show for the first time that the host specificity of E. ranae is restricted to the genus Rana and that isolates from tadpoles and adults are conspecific. Disappearance of infection during metamorphosis was confirmed experimentally, suggesting that infections in adults result from reinfections. Poikilotherm-host Eimeria species possessing a Stieda body (SB) are for the first time included in a molecular phylogenetic analysis. Eimeria ranae and Eimeria arnyi from a colubrid snake form together a well-supported clade, basal to other SB-bearing coccidia. The other analysed reptile-host eimerians, Eimeria tropidura and Choleoeimeria sp., which possess bivalved sporocysts and lack a SB, represent a distinct basal lineage of the eimeriid clade. The third part of the article reviews anuran-host Eimeria. Three distinct oocyst morphotypes, apparently correlating with the character of endogenous development, are recognized and characterized among anuran eimeriids.
Keywords: DNA, Protozoan; Coccidiosis; Coccidia; fylogeneze; Animals; molekulární sekvence - údaje; kokcidióza; Ranidae; Molecular Sequence Data; Eimeria; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; zvířata; protozoální DNA